BIOMATERIALS: the synthetic biology applied to architecture - Violano, Antonella; Ciravoglu, Aysen; Erkenez, Semin; Montaniero, Veronica; Verde, Francesca (SCUOLA PITAGORA EDITRICE, 2015)
Currently, our planet is suffering for problems related to overpopulation, accumulation of waste, depletion of raw materials, extreme exploitation of the productive soil and reckless issuance of pollutants in air, soil and water to such an extent as to make the habitat less and less suitable for the survival of living organisms. Thus, project interventions are necessary in order to safeguard first the natural environment so that an adequate social and economic development is possible. In this context, the role of architecture can be significant. It is believed that 'making architecture' today means to search for harmony between man, environment and built through cradle-to-cradle sustainable projects that cleverly use natural resources in order to restore the ecological cycles compromised by the destructive impact of the human species. Scientific knowledge acquired in biotechnology and engineering allow us to achieve this goal by working with natural systems and benefiting from them, without destroying the integrity and the capacity for renewal. A new branch of biological sciences, named synthetic biology, will be able to imagine and build new living systems for useful purposes, according the approach: House like a tree. The paper illustrates the contribution of this new discipline to the construction sector and analyses the performances of some kind of biomaterials that offer a paradigm shift in the perception of buildings from mechanical entities to living or like-living organisms. This study discussed how transformation could be achieved with the help of the sustainable design approach and environmental philosophy. The environmentalist discourse has an ideological influence on architectural approaches, as well as shaping these. Thus, we urgently have to change our conceptions about nature, such as human-centrism and the control-over-nature approach. We have to talk about new ways of collaborating with nature.
Keywords: Biomaterial; LCA; technological design; sustainable architecture; Architecture; Art